ANALISIS PUTUSAN MAHKAMAH AGUNG NO. 46/P/HUM/2018 MENGENAI LARANGAN MANTAN TERPIDANA KORUPSI MENJADI BAKAL CALON LEGISLATIF - Listijowati, Listijowati (Res Judicata, 2020)
The promulgation of the General Election Commission Regulation Number 20 of 2018 has caused controversy because it is deemed not to comply with the existence of the Constitutional Court Decision Number 42/PUU-VIII/2015 which revokes the prohibition for former convicts of corruption, narcotics, and pedophilia to become legislative candidates. Against the enactment of this regulation, a judicial review was submitted and in the Supreme Court Decision No: 46P/HUM/2018 the panel of judges stated that Article 4 paragraph (3) contradicts a higher regulation and does not have binding legal force and does not apply generally. This study analyzes the position of former corruption convicts as legislative candidates and the decision ratio of the Supreme Court No: 46/P/HUM/2018. This research is a normative legal research using a statutory approach, a conceptual approach and a case approach. The results of the study show that former corruption convicts should not be legislative candidates. Regulations on limiting the political rights of a citizen must be contained in law, not regulated in statutory regulations under law.